Köln Kunst 88 : Kunst aus Köln : Malerie - Plastik - Graphik - Video - Foto - Installation - Performance. - Josef-Haubrich-Kunsthalle? kÔLN; BBK-Stapelhaus, Köln (Köln : BBK (Berufsverband Bildender Künstler), Köln, 1988)
Aring, Rainer ; Baldegger, Markus ; Barzen, Rainer ; Becker, Krimbild ; Bolourie, Misha ; Breloh, Heinz ; Cardaun, Gisela ; Cordone, Roberto ; Demnig, Gunter ; Dillbohner, Christel ; Erlenhoff, Anke ; Felber, Gina Lee ; Fischer-Beglückter, Ruth R. ; Frohnapfel, Doris ; Gruber, Bettina ; Hasucha, Christian ; Heidelbach, Karl Horky, Ulla ; Kaluza, Katrin ; etc.
Köln Kunst 88 : Kunst aus Köln : Malerie - Plastik - Graphik - Video - Foto - Installation - Performance, Josef-Haubrich-Kunsthalle ; BBK-Stapelhaus, Köln, 16.11. - 31.12.1988
boek
Keywords: Duitsland; Köln